THEORETICAL DFT STUDY OF TASPINE'S PROPERTIES AND ITS INTERACTION WITH ACETYLCHOLINESTERASE THROUGH MOLECULAR DOCKING AND MOLECULAR DYNAMICS - Rengifo Maravi, Joel C. (2024)
In this theoretical work, computational chemistry is employed to study the properties of the molecule Taspine and its potential as an inhibitor of the enzyme acetylcholinesterase (AChE), a key target in the treatment of neurodegenerative diseases such as Alzheimer’s and Parkinson’s. The study is divided into three phases. In the first phase, Density Functional Theory (DFT) is used to analyze the global and local chemical descriptors of Taspine, with the aim of characterizing its reactivity and electronic behavior. In the second phase, a molecular docking study is performed between Taspine and acetylcholinesterase to evaluate the binding affinity and propose potential interactions that stabilize the complex. Finally, in the third phase, molecular dynamics simulations are carried out to examine the stability of the formed complex and its behavior over time, providing a deeper understanding of the interaction between both molecules. The results of this study provide valuable insights into the properties of Taspine and its capacity to inhibit AChE, which could be useful in designing future inhibitors in the field of pharmacology.